The Role of Patient Satisfaction, Technology Usability, and Healthcare Accessibility in Telemedicine Adoption: A Correlational Study - Revilla, Devin; Prado, Nenita (Journal of Interdisciplinary Perspectives, 2024)
Telemedicine has transformed healthcare delivery, improving patient satisfaction, technology usability, and accessibility. However, gaps remain in understanding patient perspectives on adoption. Most studies emphasize technological and clinical outcomes, with limited focus on how satisfaction, usability, and accessibility interact. Additionally, research on these factors in underserved regions like the Davao Region, where healthcare disparities persist, is scarce. This study investigates the factors influencing telemedicine adoption among patients, specifically focusing on patient satisfaction, technology usability, and healthcare accessibility. Utilizing a quantitative descriptive-correlational design, data were collected from 300 telemedicine users in the Davao Region through validated questionnaires. The analysis revealed significant correlations between telemedicine adoption and the examined variables, with healthcare accessibility exhibiting the strongest correlation (0.820), followed by technology usability (0.749) and patient satisfaction (0.678). Key factors impacting patient satisfaction included the quality of care, perceived similarity to face- to-face interactions, and positive perceptions of healthcare-provider interactions. Furthermore, usability factors such as ease of use, reliability, and interface quality were critical in driving engagement. The findings underscore the importance of enhancing patient satisfaction, improving technology usability, and ensuring healthcare accessibility to facilitate telemedicine adoption. Recommendations include investing in user- friendly platforms, improving service availability and affordability, and increasing awareness among potential users. By addressing these factors, stakeholders can enhance telemedicine's role in healthcare delivery, ultimately improving patient outcomes and access to medical services, particularly in underserved areas.